Penyelesaian Sengketa Umat Beragama Berbasis Moderasi Beragama di Kota Pekalongan Studi Kasus Kerusuhan November 1995 - Amrina Rosyada; Wahyu Sukma Dewi; Ayu Dwi Srikanthi; Achmad Tubagus Surur (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Settlement of Religious Disputes Based on Religious Moderation in Pekalongan City Case Study of November 1995 Riots, the author discusses the problem of how the Role of Religious Moderation in resolving inter-religious conflicts that occurred in Pekalongan City in the November 1995 riots. This research was conducted to obtain an analysis of religious disputes through a qualitative method with a case study approach. The conflict involved ethnic Chinese and indigenous Javanese. With the conditions where the majority of Perkalongan residents are Muslims who have a high religious level. When a Chinese man who was rumored to have torn and urinated on the Qur'an made the Muslim Javanese ethnic angry, resulting in riots for 3 days. This incident was motivated by several factors such as political, social, and economic differences that caused latent conflict (a situation that seems like there is no conflict, but there are actually many problems hidden and classified as difficult to handle). This was triggered by the presence of an ethnic Chinese person who was suspected of having a mental disorder (ODGJ). This led to a riot in Pekalongan City on November 22-24, 1995. The incident was handled by the Pekalongan city government, security forces, and the local community.